Fostering Critical Thinking in Vocational Accounting Education: A Quasi-Experimental Study of Guided Inquiry Learning - Nunuk Indarti; Rosmiza Bidin; Churin In; Nurus Sobakh (FKIP Universitas Lampung, 2026)
This study aims to investigate the influence of a guided inquiry learning model on students’ critical thinking skills in accounting at a vocational high school. This study adopted a quantitative approach using a quasi-experimental pretest–posttest control-group design. The participants consisted of Grade X accounting students at SMKN Grati Pasuruan, Indonesia, that is divided into an experimental and a control group. The experimental group received instruction through guided inquiry learning, while the control group received conventional teaching and learning activities. The data were gathered using a structured written test consisting of case-based essays and short analytical response items designed to assess selected indicators of critical thinking in accounting contexts. Furthermore, the data were analyzed for normality and homogeneity, followed by an ANCOVA test. The results indicate a significant difference in critical thinking between the two groups. Students in the experimental group achieved higher post-test scores (M = 81.74) than those in the control group (M = 77.09). The ANCOVA analysis remarked that the learning model had a significant effect on students’ critical thinking skills after controlling for pre-test scores (F = 7.28; p = 0.009). In addition, the pre-test covariate influenced post-test outcomes (F = 5.67; p = 0.020). The findings indicate that students who participated in inquiry-oriented instruction showed greater engagement in several activities than those in conventional learning. The study finds that guided inquiry learning is closely associated with students' critical thinking ability in accounting compared to conventional instruction. Students who participated in guided inquiry had improved post-test outcomes, indicating better performance on the assessed analytical and reasoning-based test components. This remark suggests that inquiry-oriented training fosters analytical reasoning and evidence-based problem-solving. Keywords: critical thinking, guided inquiry learning, vocational high school, accounting students.